Ethyl 8-chloro-1-cyclopropyl-6,7-difluoro-4-oxo-1,4-dihydroquinoline-3-carboxylate - Sun, Hong-shun (International Union of Crystallography, 2011)
In the molecule of the title compound, C(15)H(12)ClF(2)NO(3), the quinoline ring system is not planar, the dihedral angle between the pyridine and benzene rings being 3.55 (8)°. In the crystal, intermolecular C—H⋯O hydrogen bonds link the molecules into layers parallel to (101).